2003
DOI: 10.1021/jo0343174
|View full text |Cite
|
Sign up to set email alerts
|

Radical Cyclization by Ipso Substitution of the Methoxy Group:  Considerable Effect of HMPA on Samarium-Mediated Cyclization

Abstract: Alkyl radicals generated by treatment of thiocarbamates of conformationally favorable 3-alkyl-3-arylpropan-1-ols with tris(trimethylsilyl)silane and AIBN efficiently undergo intramolecular ipso substitution of the methoxy group, yielding the corresponding cyclized products. In contrast, either conformationally favorable or flexible 1-arylalkan-3- or 4-ones easily cyclize into five- or six-membered condensed rings by treatment with SmI(2) via ketyl radical intermediates. The addition of HMPA as cosolvent dramat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 26 publications
(17 reference statements)
0
15
0
Order By: Relevance
“…Tanaka et al also studied substrates with two or more substituents, in particular the combination of alkoxycarbonyl substituents and methoxy groups. [30] They could demonstrate that in the absence of HMPA the coordination of samarium(II) diiodide to o-methoxy groups has a strong influence on the reaction outcome, mainly leading to ipsosubstitutions. In the presence of the strong ligand HMPA the interaction of Sm II with the oxygen containing substituents should be less important.…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka et al also studied substrates with two or more substituents, in particular the combination of alkoxycarbonyl substituents and methoxy groups. [30] They could demonstrate that in the absence of HMPA the coordination of samarium(II) diiodide to o-methoxy groups has a strong influence on the reaction outcome, mainly leading to ipsosubstitutions. In the presence of the strong ligand HMPA the interaction of Sm II with the oxygen containing substituents should be less important.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that the ketyl radical ipso substitution reaction of an aromatic methoxy group is effectively promoted by SmI 2 without HMPA to afford cyclized products. 17 Thus, we examined the reaction of 7h with LiBr instead of HMPA or without an additive. Unexpectedly, the yield of the ipso-substituted product was decreased or null compared with that when HMPA was used (entries 12 and 13 vs entry 11).…”
Section: Cyclization Of 1-benzoyl-23-dihydro-7-iodoindolesmentioning
confidence: 99%
“…Although space restriction does not permit a detailed description, our group developed some other interesting novel reactions such as (1) stereoselective synthesis of 1,3-amino alcohols via allenylindium reagents using 2-ethynylaziridines as chiral carbon nucleophiles, 143,144) (2) samarium(II)-mediated radical cyclization onto an aromatic group, [174][175][176][177][178] (3) synthesis and isomerization of vinylaziridines and their application to the stereoselective synthesis of (E)-alkene dipeptide isosteres. [64][65][66][67]179,180) The author hopes the presented reactions based on the novel reactivities of allenes will facilitate further development of allene chemistry [181][182][183] and application to synthesis of pharmacologically important compounds from this class of compounds.…”
Section: Resultsmentioning
confidence: 99%